Cysteine dioxygenase structures from pH 4 to 9: consistent Cys-persulfenate formation at intermediate pH and a Cys-bound enzyme at higher pH - Driggers, Camden M. (2013)
Mammalian cysteine dioxygenase (CDO) is a mononuclear non-heme iron protein that catalyzes the conversion of cysteine (Cys) to cysteine sulfinic acid (CSA) by an unclarified mechanism. One structural study revealed a Cys-persulfenate (or Cys-persulfenic acid) formed in the active site, but quantum mechanical calculations have been used to support arguments that it is not an energetically feasible reaction intermediate. Here, we report a series of high-resolution structures of CDO soaked with Cys at pH values from 4 to 9. Cys binding is minimal at pH≤5 and persulfenate formation is consistently seen at pH values between 5.5 and 7. Also, a structure determined using laboratory-based X-ray diffraction shows that the persulfenate, with an apparent average O-O separation distance of ~1.8 Å is not an artifact of synchrotron radiation. At pH≥8, the active site iron shifts from 4- to 5-coordinate, and Cys soaks reveal a complex with Cys, but no dioxygen, bound. This ‘Cys-only’ complex differs in detail from a previously published ‘Cys-only’ complex which we reevaluate and conclude is not reliable. The high-resolution structures presented here do not resolve the CDO mechanism, but do imply that an iron-bound persulfenate (or persulfenic acid) is energetically accessible in the CDO active site, and that CDO active site chemistry in the crystals is influenced by protonation/deprotonation events with effective pKa values near ~5.5 and ~7.5 that influence Cys binding and oxygen binding/reactivity, respectively. Furthermore, this work provides reliable ligand-bound models for guiding future mechanistic considerations.